2009
DOI: 10.1038/ejhg.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in an alternative untranslated exon of hexokinase 1 associated with Hereditary Motor and Sensory Neuropathy – Russe (HMSNR)

Abstract: Hereditary Motor and Sensory Neuropathy -Russe (HMSNR) is a severe autosomal recessive disorder, identified in the Gypsy population. Our previous studies mapped the gene to 10q22-q23 and refined the gene region to B70 kb. Here we report the comprehensive sequencing analysis and fine mapping of this region, reducing it to B26 kb of fully characterised sequence spanning the upstream exons of Hexokinase 1 (HK1). We identified two sequence variants in complete linkage disequilibrium, a G4C in a novel alternative u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 42 publications
0
50
0
1
Order By: Relevance
“…Although PKP2 transcript and protein from proband A-1 heart tissue were partially degraded owing to poor tissue conservation, we showed that exon 6 splicing was normal in the presence of this variant and did not induce an allele-specific misexpression. As this variant was exclusively identified in patients with ARVC and not in controls, we finally hypothesised that this variant might be in linkage disequilibrium with another non-exonic causative PKP2 mutation that would have been missed by our restricted exonic sequencing protocol 30. We found no additional mutation in the PKP2 regions potentially implicated in transcript expression or stability.…”
Section: Discussionmentioning
confidence: 76%
“…Although PKP2 transcript and protein from proband A-1 heart tissue were partially degraded owing to poor tissue conservation, we showed that exon 6 splicing was normal in the presence of this variant and did not induce an allele-specific misexpression. As this variant was exclusively identified in patients with ARVC and not in controls, we finally hypothesised that this variant might be in linkage disequilibrium with another non-exonic causative PKP2 mutation that would have been missed by our restricted exonic sequencing protocol 30. We found no additional mutation in the PKP2 regions potentially implicated in transcript expression or stability.…”
Section: Discussionmentioning
confidence: 76%
“…Caused by mutations in hexokinase 1 or HK1, CMT4G clinical phenotype is characterized by distal lower limb weakness by the first decade with distal upper limb weakness evolving variably from the end of the first decade to the third decade [140,141]. By adolescence proximal lower limbs are usually weak.…”
Section: Cmt4gmentioning
confidence: 99%
“…Tal entidade foi inicialmente chamada de neuropatia sensitiva e motora hereditária Russe (HMSNR). Estudos posteriores mostraram que essa variante (CMT4G) estava ligada a uma mutação no cromossomo 10q23.2, especificamente no gene HK1 61 . O gene HK1 codifica um hexoquinase, que cataliza a primeira etapa no metabolismo da glicose.…”
Section: Cmt4gunclassified